Pengaruh Kualitas Produk Dan Promosi Melalui Media Sosial Terhadap Keputusan Pembelian Pizza Hut Cempaka Putih Jakarta Pusat - Indah Dwi Cahyani; Redjeki Agoestyowati (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aimed to determine the effect of product qualities and promotions through social media on buying decisions in Pizza Hut Cempaka Putih, Central Jakarta. The population in this study were all consumers of Pizza Hut Cempaka Putih. This study used a quantitative research by distributing questionnaires to 150 samples of respondents using accidental sampling technique. The data collection technique used is a questionnaire, where each respondent is given 30 questions. The data was tested using validity and reliability tests, which also went through the classical assumption test. Furthermore, the data analysis test was carried out using multiple regression analysis, T-test, F-test, and coefficient of determination. The results showed that based on hypothesis testing using the T test, product qualities and promotions through social media has a positive and significant results on buying decisions. Meanwhile, the results tested using the F-test, indicates that all the independent variables in this study has a significant effect on buying decisions. The coefficient of determination (R2) resulted in 0.469, which means that the effect of product qualities and promotions are 46.9%, while the remaining 53.1% is influenced by other variables not examined in this study